Concert mondial de linguistique française (ENS Éditions, 2023)
This collective work is a tribute to Franck Neveu, a leading expert and professor of language sciences, whose original thinking and extensive academic contribution will have a lasting impact on research in linguistics. In linguistics and/or in language sciences, because this is an old and constantly recurring debate. Franck Neveu resolutely pronounced himself in favour of the latter, although he positioned himself, equally resolutely, as a linguist. This collective volume pays tribute to this open-mindedness by bringing together contributions from renowned authors close to the dedicatee, who explore not only his areas of specialisation such as syntax, semantics and the epistemology of language sciences, but also neighbouring disciplines such as dialectology or text genetics. It has the work of Franck Neveu as its unifying theme and is intended to promote French linguistics, which he champions and illustrates. Thanks to its contributions which represent current research, this book will be of interest to both a specialist audience and one that is keen to learn about language sciences.